Natação para escolares: da motivação ao controle da ansiedade na pratica - Ferrari, Gustavo Pereira de Avila [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
More and more young people start their sports practice whether in the school system or outside. If on one hand this is a positive factor and motivating children and young people. on the other hand it can generate a level of precocious specialization and anxiety if they overvalue the competition and overcome it, where they are submitted to repetitive training leading to the abandonment of the practice of the sports modality. The present study had as objective to make a bibliographical survey of studies that approach the swimming for schoolchildren. Also, focus on how the practice of this modality can be beneficial in this period of life or interfere in performance in both sports and school performance. A literature review was made and we can conclude that the physical educator, parents and teachers have to be attentive to the reactions of the students, be they athletes or PE students to minimize the effects of negative anxiety and create a stimulating and motivator for sports practice, in the case of school swimming.

Cada vez mais jovens iniciam a prática esportiva, quer seja no sistema escolar ou fora dele. Se por um lado, este é um fator positivo e motivador as crianças e jovens. por outro pode gerar um nível de especialização precoce e ansiedade se supervalorizar a competição e o vencer, onde são submetidos a treinos repetitivos levando ao abandono da prática da modalidade esportiva. O presente estudo teve por objetivo fazer um levantamento bibliográfico de estudos que abordam a natação para escolares. Além disso, enfocar como a prática desta modalidade, pode ser benéfica neste período da vida ou interferir no desempenho tanto no esporte, como no rendimento dos escolares. Foi feita uma revisão de literatura, e podemos concluir que o educador físico, pais e professores tem que ficar atentos as reações dos escolares, sejam eles atletas ou alunos de Educação Física, para diminuir ao máximo possível, os efeitos da ansiedade negativa e criar um ambiente estimulante e motivador para prática do esporte, no caso, da natação escolar.
Keywords: Natação; Ansiedade; Educação fisica; Swimming